The impacts of work commitment and school climate on the teacher performance of public primary schools - Dahliawati; Syahril; Rifma; Irsyad (Universitas Jambi, Indonesia, 2023)
This research aimed to analyze the influence of work commitment and school climate on the teacher performance of public primary school. This research used a quantitative correlational associative type of method. The population was 117 primary school teachers. Samples were taken using a proportional stratified random sampling technique. The research instrument used a Likert scale model questionnaire with a trial with a population of 20 students out of the sample. The test results showed that the instrument was valid. Research data were analyzed using the means to describe the data and test requirements, namely normality, homogeneity, and multicollinearity. Descriptive results of teacher performance were 89.09%, work commitment 86.88%, and school climate 75.91%. Data analysis showed an influence of work commitment on teacher performance of 12.6%, an influence of school climate and teacher performance of 10.1 and a significant influence of work commitment and school climate jointly on teacher performance of 34.4%.